The Transcriptome and DNA Methylome Landscapes of Human Primordial Germ Cells - Guo, Fan; Yan, Liying; Guo, Hongshan; Li, Lin; Hu, Boqiang; Zhao, Yangyu; Yong, Jun; Hu, Yuqiong; Wang, Xiaoye; Wei, Yuan; Wang, Wei; Li, Rong; et al. (Cell, 2015)
Germ cells are vital for transmitting genetic information from one generation to the next and for maintaining the continuation of species. Here, we analyze the transcriptome of human primordial germ cells (PGCs) from the migrating stage to the gonadal stage at single-cell and single-base resolutions. Human PGCs show unique transcription patterns involving the simultaneous expression of both pluripotency genes and germline-specific genes, with a subset of them displaying developmental-stage-specific features. Furthermore, we analyze the DNA methylome of human PGCs and find global demethylation of their genomes. Approximately 10 to 11 weeks after gestation, the PGCs are nearly devoid of any DNA methylation, with only 7.8% and 6.0% of the median methylation levels in male and female PGCs, respectively. Our work paves the way toward deciphering the complex epigenetic reprogramming of the germline with the aim of restoring totipotency in fertilized oocytes. [Display omitted] •The transcriptomes of human PGCs are relatively homogeneous between 4 and 11 weeks•The inactivated X chromosomes in PGCs are already reactivated in 4 week embryos•Individual meiotic PGCs exhibit strongly heterogeneous gene expression patterns•The global erasure of DNA methylation in human PGCs is completed at 10 to 11 weeks The transcriptome of human primordial germ cells from the migrating stage to the gonadal stage reveals that both pluripotency genes and germline-specific genes are simultaneously expressed within the same individual cells. The global erasure of DNA methylation creates a super-hypomethylated germline genome.